2015
DOI: 10.1371/journal.pone.0129047
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi-Localized γ-Ear-Containing ARF-Binding (GGA) Proteins Alter Amyloid-β Precursor Protein (APP) Processing through Interaction of Their GAE Domain with the Beta-Site APP Cleaving Enzyme 1 (BACE1)

Abstract: Proteolytic processing of amyloid-β precursor protein (APP) by beta-site APP cleaving enzyme 1 (BACE1) is the initial step in the production of amyloid beta (Aβ), which accumulates in senile plaques in Alzheimer’s disease (AD). Essential for this cleavage is the transport and sorting of both proteins through endosomal/Golgi compartments. Golgi-localized γ-ear-containing ARF-binding (GGA) proteins have striking cargo-sorting functions in these pathways. Recently, GGA1 and GGA3 were shown to interact with BACE1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The GGA family genes were implicated in both PG and GG; GGA2 was downregulated in both and GGA3 upregulated in the GG. GGA depletion has been shown to have a missorting effect on mannose‐6‐phosphate receptors, cathepsin D and APP secretory inhibition, which was one of the top hits in our master gene list. In HeLa cells, it was found that overexpression of GGA's increases fragmentation and vacuolization of the trans‐Golgi network implying that these proteins have a role in maintaining Golgi integrity .…”
Section: Resultsmentioning
confidence: 99%
“…The GGA family genes were implicated in both PG and GG; GGA2 was downregulated in both and GGA3 upregulated in the GG. GGA depletion has been shown to have a missorting effect on mannose‐6‐phosphate receptors, cathepsin D and APP secretory inhibition, which was one of the top hits in our master gene list. In HeLa cells, it was found that overexpression of GGA's increases fragmentation and vacuolization of the trans‐Golgi network implying that these proteins have a role in maintaining Golgi integrity .…”
Section: Resultsmentioning
confidence: 99%
“…The yeast GGA1 protein has been implicated in binding ubiquitin, thus facilitating the sorting of cargo proteins from the trans-Golgi network to endosomal compartments (Takatsu et al, 2002; Zhdankina et al, 2001). Human GGA1 overexpression attenuates amyloidogenic processing of amyloid precursor proteins (APP) in Alzheimer’s disease and a rare inherited lipid-storage disease, Niemann-Pick type C (NPC) (Kosicek et al, 2014; von Einem et al, 2015). Finally, SIS1 , the yeast Hsp40 homolog of human DNAJ/HSP40 family proteins, was identified as αSyn suppressor via PRISM.…”
Section: Resultsmentioning
confidence: 99%
“…APP695 CMV(myc) is described in Kinoshita et al [30]. BACE-phCMV3(HA) is described in von Einem et al [31]. pUltra-hot is a lentiviral vector backbone for bi-cistronic expression of the gene of interest and the fluorescent reporter mCherry under the control of a human ubiquitin promoter.…”
Section: Methodsmentioning
confidence: 99%